2010
DOI: 10.1083/jcb.20090808620100331c
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride inhibits macropinocytosis by lowering submembranous pH and preventing Rac1 and Cdc42 signaling

Abstract: Figure 2. (B) Top: schematic of the structure of membrane-targeted SEpHluorin/mCherry chimaera used to measure pH sm . Bottom: confocal images of SEpHluorin (left) and mCherry fluorescence (right) in A431 cells. Bar, 10 µm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
265
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(280 citation statements)
references
References 0 publications
11
265
1
3
Order By: Relevance
“…As a clinical inhibitor of the Na + /H + exchanger, EIPA plays an important role in macropinocytosis formation (Koivusalo et al, 2010), and wortmannin is a covalent inhibitor of phosphatidylinositol 3-kinases (PI3K), which is involved in multiple stages of macropinocytosis (Mercer and Helenius, 2012). Therefore, we used EIPA and wortmannin to clarify the role of macropinocytosis and PI3K in PSV entry and infection.…”
Section: Psv Entry Does Not Depend On Macropinocytosis But Requires Pi3kmentioning
confidence: 99%
“…As a clinical inhibitor of the Na + /H + exchanger, EIPA plays an important role in macropinocytosis formation (Koivusalo et al, 2010), and wortmannin is a covalent inhibitor of phosphatidylinositol 3-kinases (PI3K), which is involved in multiple stages of macropinocytosis (Mercer and Helenius, 2012). Therefore, we used EIPA and wortmannin to clarify the role of macropinocytosis and PI3K in PSV entry and infection.…”
Section: Psv Entry Does Not Depend On Macropinocytosis But Requires Pi3kmentioning
confidence: 99%
“…Both require phosphoinositide 3-kinase (PI3K) signaling (Araki et al, 1996), phospholipase Cγ (Amyere et al, 2000;Cheeseman et al, 2006), Rac1 (Caron and Hall, 1998;Ridley et al, 1992), and dynamin (Liu et al, 2008;Cao et al, 2007;Gold et al, 1999;Tse et al, 2003), making differentiation between the two processes by targeting components difficult. The only macropinocytosis specific inhibitor, EIPA, functions by deregulating intracellular pH and thus may disrupt additional aspects of the viral life cycle that contribute to inhibition of virus infection (Koivusalo et al, 2010).…”
Section: Uptake Of Apoptotic Bodies By Pveers and Implications For VImentioning
confidence: 99%
“…Two separate groups have shown that HIV-1 replication is reduced in macrophages infected in the presence of amiloride derivatives such as DMA and EIPA (24,25). These drugs specifically inhibit macropinocytosis by acting on Na (ϩ) /H (ϩ) exchange and submembranous pH, thereby affecting F-actin remodeling (36). The authors concluded that macropinocytosis is involved in HIV-1 infection in such cells.…”
Section: Macropinocytosis Is Involved In Hiv-1 Endocytosis In Macrophmentioning
confidence: 99%